Knowledge and practices of bed sore prevention among staff nurses working in a selected hospital, Ludhiana, Punjab, India - Shrestha, R (Journal of Chitwan Medical College, 2017)
The majority of pressure ulcers are preventable. Nurses should be able to constantly observe their client’s skin for breaks or impairment in skin integrity. Pressure ulcers not only cause suffering to the patients but also increases nurses’ workload in clinical setting. Prevention of pressure ulcers is a significant nursing concern to reduce the costs of treatment and patients’ suffering. To assess the level of knowledge and observe the practices of bed sore prevention among staff nurses working in general wards as well as special units. A descriptive, cross sectional and participating observational method was adopted. This study was conducted in Christian Medical College & Hospital, Ludhiana, Punjab, India among 60 staff nurses working in general wards and special units. Non probability, purposive sampling technique was used. Semi structured self administered questionnaire was developed for assessing knowledge and observation checklist was developed for practice of bed sore prevention for data collection procedure. Data were entered in SPSS 17.0 version and analyzed using in terms of descriptive (Frequency, percentage, mean, standard deviation and mean percentage) and inferential statistics (Independent t test, ANOVA and correlation). Findings highlight a difference in knowledge between special (73%) and general (62%) based nurses regarding pressure ulcers. Similar results were also found for practice. Overall discrepancies between knowledge (68%) and practice (53%) were reported for staff nurses regarding bed sore prevention. The results showed special unit nurses’ practice significantly better (60.29%) than general ward nurses (46.68%). Although 40% of overall staff nurses achieved excellent level on knowledge, none of them crossed the excellent level on practice. It is concluded that knowledge and practice of bed sore prevention among nurses working within specialists and generalist ward differed and a theory practice gap exists which has implications for patients care suggesting the need for a specific educational intervention to respond to this need.